Using mobile methods to understand multifaceted heritage organisations. Issue 4 (29th November 2019) - Johnstone, Jane Hamilton; Bryce, Derek; Alexander, Matthew J.
Abstract : Purpose: This paper aims to evaluate the possibilities associated with go-along technique and other mobile qualitative methods augmenting other qualitative methods as a novel approach to developing understanding of multifaceted organisations. Design/methodology/approach: The study explores the challenges associated with "static" qualitative methods for understanding multifaceted organisations and evaluates how a range of mobile methods can achieve a greater depth of analysis when researching complex hospitality and tourism settings. The paper uses an illustrative empirical case where mobile methods are used as part of a multi-method qualitative study exploring ancestral tourism in a large, heterogeneous tourism organisation. Findings: This research highlights how mobile methods can service to: broaden the scope of interviews through introducing enhanced meaning and spontaneity; afford opportunity to explore and verify interview findings in informal settings; and widen participation in the study through ongoing recruitment of participants. Practical implications: The authors identify implications for researchers working within hospitality and tourism who can gain additional insight by augmenting qualitative studies with mobile methods. Originality/value: This paper identifies challenges in using more static qualitative methods when seeking understanding of complex, multifaceted tourism organisations where work activities are mobile and spatially dispersed. This research highlights the value of mobile methods in combination with other qualitative methods, to gain greater understanding of these organisations.